Heterogeneous Gold Catalysts and Catalysis 2014
DOI: 10.1039/9781782621645-00001
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Gold Nanoparticles by Solid Supports

Abstract: Catalysis by supported gold nanocatalysts has attracted much attention recently. However, gold nanoparticles tend to sinter under realistic conditions (e.g., under elevated temperatures or in reaction media), leading to degraded activity. Although there are many excellent reviews covering various aspects of gold catalysis, few have focused on the stabilization of gold nanoparticles on solid supports. Here we summarize several synthesis strategies for the stabilization of gold nanoparticles on solid supports, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 147 publications
(110 reference statements)
0
11
0
Order By: Relevance
“…There are a few reports on the growth of Au nanoparticles supported on TiO 2 upon high-temperature treatment and under oxidizing atmosphere [7]. Akita et al reported that Au nanoparticles of 2.1 nm on TiO 2 grew to 9.7-nm particles upon calcination in air at 600°C for 4 h [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are a few reports on the growth of Au nanoparticles supported on TiO 2 upon high-temperature treatment and under oxidizing atmosphere [7]. Akita et al reported that Au nanoparticles of 2.1 nm on TiO 2 grew to 9.7-nm particles upon calcination in air at 600°C for 4 h [32].…”
Section: Discussionmentioning
confidence: 99%
“…Gold is the most active catalyst for CO oxidation at room temperature which makes Au catalysts very interesting for this application [2][3][4][5][6]. However, when the engine becomes hot, it reaches the temperatures as high as 700°C, and high-temperature treatment often causes growth of Au nanoparticles [7][8][9][10][11][12][13][14]. For bulk Au, the melting point is 1064°C, and the Hüttig temperature at which surface atoms become mobile is 319°C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these earlier studies, it is generally difficult to control the deposition and dispersion of metal nanoparticles on the oxide surfaces [13][14][15]. Horvath et al [16] employed two different methods to mitigate such an issue.…”
Section: Introductionmentioning
confidence: 99%
“…A wellknown is the fact that unique properties of nanoparticles are related with their stability. One method for stabilization the metallic nanoparticles is their deposition on a solid support [11]. The specific properties of solid material may determine the final properties of the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%